2020
DOI: 10.1038/s41598-020-74749-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel and potent antimicrobial effects of caspofungin on drug-resistant Candida and bacteria

Abstract: Echinocandins, including caspofungin, micafungin, and anidulafungin, are first-line antifungal agents for the treatment of invasive candidiasis. They exhibit fungicidal activity by inhibiting the synthesis of β-1,3-d-glucan, an essential component of the fungal cell wall. However, they are active only against proliferating fungal cells and unable to completely eradicate fungal cells even after a 24 h drug exposure in standard time-kill assays. Surprisingly, we found that caspofungin, when dissolved in low ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Here, we demonstrate that MF acts in a different way; our experimental evidence with MF strongly supports that this antifungal does not induce ROS formation or increase antioxidant enzyme activities or gene expressions ( Figure 2 , Figure 4 and Figure 5 ) [ 27 ], albeit MF exhibits fungicidal activity against C. albicans . Supporting these data, CAS was the only echinocandin able to induce mitochondrion-derived ROS in the filamentous fungus Aspergillus fumigatus [ 47 ] and to undergo conformational changes in low ionic solution with a subsequent increase of its toxicity, attributed to a higher ROS production, in multidrug resistance Candida and bacteria cells [ 48 ]. In order to fortify our conclusions, we made use of mutants defective in the MAPK Hog1, which are hypersensitive to oxidants [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that MF acts in a different way; our experimental evidence with MF strongly supports that this antifungal does not induce ROS formation or increase antioxidant enzyme activities or gene expressions ( Figure 2 , Figure 4 and Figure 5 ) [ 27 ], albeit MF exhibits fungicidal activity against C. albicans . Supporting these data, CAS was the only echinocandin able to induce mitochondrion-derived ROS in the filamentous fungus Aspergillus fumigatus [ 47 ] and to undergo conformational changes in low ionic solution with a subsequent increase of its toxicity, attributed to a higher ROS production, in multidrug resistance Candida and bacteria cells [ 48 ]. In order to fortify our conclusions, we made use of mutants defective in the MAPK Hog1, which are hypersensitive to oxidants [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans is one of the most common reasons of Candida infections, also causing high mortality and morbidity in immunocompromised patients ( 38 ). A mortality of 40% has been reported in patients with invasive candidiasis, even with the proper treatment with current antifungal drugs ( 39 ). Antifungal vaccine is the primary method of prevention, especially for those with weakened immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Authors reported interference of aprepitant/itraconazole with metal ion homeostasis, which led to losing reactive oxygen species' detoxification ability [114]. [115,116] Biofilms formed by Candida spp. on indwelling catheters are difficult to treat.…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%
“…This strategy was selected in the work of Sumiyoshi and colleagues. Caspofungin was dissolved in low ionic solutions and a considerable reduction of candidal (including resistant C. auris) was noticed in the polymicrobial biofilms present in the catheter-lock therapy model [116].…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%